Effect of multiple intravitreal injections of conbercept on the cornea in patients with branch retinal vein occlusion-induced macular edema - Gaixia Zhai; Tiehui Shen; Yuanzhen Su; Na Liu (Frontiers in Medicine, 2025)
BackgroundTo investigate the effect of multiple intravitreal injections of conbercept on the cornea in patients with branch retinal vein occlusion (BRVO)-induced macular edema.MethodsThe retrospective study analyzed the clinical data of 40 patients (40 eyes) with BRVO-induced macular edema between March 2020 and March 2023. All patients received intravitreal injections of conbercept according to the “3 + PRN” regimen and were followed for at least 6 months. Corneal analysis was performed using a corneal endothelial microscope and a Pentacam corneal topographic map. The best-corrected vision acuity (BCVA), central retinal thickness, central corneal thickness, corneal endothelial cell density, hexagonal cell percentage, and coefficient of variation before and at 1, 3, and 6 months after the injection were compared.ResultsThe study included 40 patients (22 males and 18 females) with an average age of 50.80 ± 7.35 years (range, 38–67 years). The corneal endothelial cell densities, central corneal thicknesses, hexagonal cell percentages, and coefficients of variation before and at 1, 3, and 6 months after the injection were not significantly different (P > 0.05). The average BCVA was significantly higher at 1, 3, and 6 months after than before the injection (P < 0.05 each). The average central retinal thickness was significantly lower at 1, 3, and 6 months after than before the injection (P < 0.05 each). The number of injections was 3.08 ± 0.27 at the last follow-up. No adverse reactions, such as endophthalmitis, retinal detachment, or thrombus, were observed in any patient after treatment.ConclusionMultiple intravitreal injections of conbercept can improve the BCVA and reduce macular edema in patients with BRVO and have no significant effect on the cornea.